Youtube as an expression to transpeople: content analysis of Stasya Bwarlele Youtube channel - Vidya Kusumawardani; Danang Trijayanto (International Journal of Communication and Society, 2020)
The paper aims to examine one of the transgender celebrities based on their YouTube videos. The method of this research was using content analysis. This method examines the video theme, transgender-specific issues, physical changing of Indonesia transgender celebrities Stasya Bwarlele’s YouTube channel during 2018-2020 with a total of 78 YouTube videos. These current studies identify that from all of 78 YouTube videos of Stasya Bwarlele’s, video themes of no trans or beauty/make-up/shopping such as daily vlog are mentioned 34 times (44%). Meanwhile, based on trans specific issues, dating themes are mentioned 19 times (28%), such as in relationship vlog. This frequency has the same value as terminology variables, which is 19 times (28%). Meanwhile, to express her gender identity as transgender, she could be seen in physical transition mentions such as surgery, which is mentioned ten times (50%). According to those variables, Stasya Bwarlele has shown that her videos indicate that she has the same videos as other YouTubers who mostly discussed daily vlog and dating. Based on the data, it has indicated that YouTube is being used by Stasya to express her daily activity (no trans or beauty/make up/shopping) as trans people, the same as a cisgender people do for traveling, cooking, shooting and modeling.